ANALISIS POTENSI DAN DAYA DUKUNG KAWASAN WISATA PANTAI MUTIARA 88 KECAMATAN PANTAI CERMIN KABUPATEN SERDANG BEDAGAI Analysis of Potensial and Carrying Capacity of Mutiara 88 Beach, Sub District of Pantai Cermin, Regency of Serdang Bedagai - Eulis Safina; Pindi Patana; Ahmad Muhtadi (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Mutiara 88 beach is located in the Kota Pari village, Sub District of Pantai Cermin, Regency of Serdang Bedagai. Mutiara 88 beach is ± 43 km from the provincial capital city and ± 25 km from the district capital. This study aims to know potensial the Mutiara 88 beach, analyze the suitability index of Mutiara 88 Beach tourism and analyze the carrying capacity of the mutiara 88 beach for the beach tourism activities and to know the tourists and citizen’s perception about the ecological quality of the Mutiara 88 beach. This research used the Purposive Sampling and Accidental Sampling method. Mutiara 88 beach has the very suitable index (S1) for catagory swim, parasailling, expose, volleyball and recreation and for catagory banana boating and fishing has suitable index (S2). The beauty value of Mutiara 88 Beach is 62% (quite beautiful) and the comfort value of Mutaiara 88 beach is 64% (comfortable enough). The carrying capacity of the Mutiara 88 beach can accommodate 240 tourists every day. While the results of fisheries can be enjoyed by visitors.Keyword : Mutiara 88 Beach, analysis suitability of area, the carrying capacity